2019
DOI: 10.3390/ijms20174273
|View full text |Cite
|
Sign up to set email alerts
|

Association of Obesity with DNA Methylation Age Acceleration in African American Mothers from the InterGEN Study

Abstract: African American women are affected by earlier onset of age-associated health deteriorations and obesity disproportionally, but little is known about the mechanism linking body mass index (BMI) and biological aging among this population. DNA methylation age acceleration (DNAm AA), measuring the difference between DNA methylation age and chronological age, is a novel biomarker of the biological aging process, and predicts aging-related disease outcomes. The present study estimated cross-tissue DNA methylation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 34 publications
4
33
0
Order By: Relevance
“…Our observations suggest that higher pre-pregnancy BMI may lead to higher biological burden relative to cellular aging. This finding is supported by existing literature in both pregnant and non-pregnant individuals, 28,33,34 and may provide insight into age-related disease outcomes. Because it is as a modifiable factor, BMI represents an important clinical target to improve outcomes.…”
Section: Discussionsupporting
confidence: 86%
“…Our observations suggest that higher pre-pregnancy BMI may lead to higher biological burden relative to cellular aging. This finding is supported by existing literature in both pregnant and non-pregnant individuals, 28,33,34 and may provide insight into age-related disease outcomes. Because it is as a modifiable factor, BMI represents an important clinical target to improve outcomes.…”
Section: Discussionsupporting
confidence: 86%
“…Nevalainen et al [42] found increased epigenetic age estimates in middle-aged individuals with high BMI. These findings were supported by data of Simpkin et al [43], McCartney et al [32], Li et al [44] and Thurston et al [29]. Recently, Fiorito et al [27] published data from a large multicohort study (n = 16,245), revealing increased epigenetic age estimates of up to 1.08 years (p < 0.001) for individuals with high BMI (BMI ≥ 30).…”
Section: Obesity Fosters Epigenetic Ageingmentioning
confidence: 52%
“…For many African Americans (AA), experiencing violence, discrimination, and environmentally induced stressors, such as childhood neglect or abuse, are well documented ( Jacobs et al., 2014 ; Pew Research Center, 2016 ). AAs carry a disproportionate burden of incidence, morbidity, and mortality from chronic diseases such as hypertension and obesity ( Allport et al., 2019 ; Barengolts et al., 2019 ; Yang et al., 2019 ; Li et al., 2019 ; Faucher et al., 2019 ; Assari et al., 2019 ; Nagy et al., 2020 ; Goode et al., 2017 ; Go et al., 2014 ) in addition to exposure to violence (ETV) which has also been shown to have a negative impact on health ( Griggs et al., 2019 ; Goldmann et al., 2011 ; Woodson et al., 2010 ; Paranjape and Kaslow, 2010 ; Mitchell et al., 2010 ; Paranjape et al., 2009 ; McGee et al., 2001 ; Moffitt and Klaus-Grawe Think, 2013 ; Olofsson et al., 2012 ). Therefore, it is worthwhile to examine if lifetime exposure to violence is a contributing factor in AA health disparity.…”
Section: Introductionmentioning
confidence: 99%